Estimation of Escherichia coli in raw ground beef. - Stiles, M E (1980)
This study was undertaken to establish and evaluate more rapid methods of estimating Escherichia coli in ground beef than the standard most probable number (MPN) technique. Direct inoculation of and modifications to EC medium gave unreliable estimates of the presumptive E. coli count. Solid media incubated at an elevated temperature were compared to the MPN technique. Anderson and Baird-Parker's tryptone bile agar (TBA) method and prepoured plates of Endo, Levine eosin methylene blue (EMB), and violet red bile (VRBA) agars incubated at 44 degree C gave equivalent counts to the standard MPN method. Anderson and Baird-Parker TBA was the most selective solid medium for E. coli estimation, but all selective media incubated at elevated temperature reduced apparent E. coli counts by as much as 50%. Indole-producing and lactose-fermenting Enterobacteriaceae, capable of growth at elevated temperature, were tested for their growth on TBA, EMB, and VRBA at elevated temperature. TBA was selective for E. coli biotype I compared to other Enterobacteriaceae that predominate in meats. VRBA and EMB incubated at elevated temperature were not as selective as TBA, but differences in colonies could be observed between typical E. coli colonies and other Enterobacteriaceae on these media. Therefore, VRBA incubated at elevated temperature is proposed as a quality assurance screening test for presumptive E. coli in ground meat. Resuscitation techniques and prepoured plates with VRBA increased recovery levels of presumptive E. coli, but, under the conditions of this study, not to levels that represented a significant practical difference.